2019
DOI: 10.1051/matecconf/201925207010
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of behaviour of compressed thin-walled Z-profiles weakened by holes

Abstract: This paper presents the results of numerical analysis conducted to investigate compressed thin-walled Z-profile weakened by holes with variable geometrical parameters. The specimens made of constructional steel were articulately supported on the edges of the cross-section in the upper and lower parts. The FEM analysis examined the nonlinear stability of these structures in the post-buckling state, where the mode of buckling was forced to ensure their stable behaviour. The numerical computations were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…This work is continuation of Author research, which part of them was published in [24][25][26][27]. The obtained results showed that we can influence on buckling and postbuckling behaviour of thinwalled columns by changing the shape and cut-out geometric parameters.…”
Section: Introductionsupporting
confidence: 52%
“…This work is continuation of Author research, which part of them was published in [24][25][26][27]. The obtained results showed that we can influence on buckling and postbuckling behaviour of thinwalled columns by changing the shape and cut-out geometric parameters.…”
Section: Introductionsupporting
confidence: 52%
“…Their results show that the size and shape of holes influences the buckling behaviour. Similar investigations were performed [19] also on profiles made of glass fibre-reinforced polymer (GFRP) materials. The present work starts from results obtained in the mentioned paper to select the configuration of holes.…”
Section: Introductionmentioning
confidence: 78%
“…The shape and dimensions of holes was choosen based on the previous work [19,20], where the influence was tested of three parameters (opening ratio, spacing ratio, and hole shape) on the buckling load. Circular shaped holes gave the highest values of critical load.…”
Section: The Study Subjectmentioning
confidence: 99%
“…The authors investigated the buckling behaviour of aluminium alloy square hollow sections (SHS) with a circular hole under web crippling. Paper [ 32 ] presents the results of numerical analysis of compressed thin-walled Z-profiles weakened by holes with variable geometrical parameters, but made of constructional steel. In [ 33 ], the authors made some analysis of H-shaped high-strength steel beams with perforated web.…”
Section: Introductionmentioning
confidence: 99%